Intercellular cancer collisions generate an ejected crystal comet tail effect with fractal interface embryoid body reassembly transformation (2011)
We have documented self-assembled geometric triangular chiral crystal complexes (GTCHC) and a framework of collagen vascular invariant geometric attractors in cancer tissues. This article shows how this system evolves in time.